2016
DOI: 10.1177/1086026616633255
|View full text |Cite
|
Sign up to set email alerts
|

A Bottom-Up Approach to Short-Term Immersion in Subsistence Marketplaces

Abstract: We discuss an international immersion research experience conducted by an interdisciplinary team of business and environmental engineering students and faculty in Tanzania. Using this experience as “data,” we bring out methodological and substantive issues in studying the intersection of poverty and the environment. The approach we describe is bottom-up, beginning with micro-level details of life circumstances. Such micro-level details are often the most challenging to learn and the most neglected in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…According to Deo et al (2023), the SDGs can be integrated into marketing education in various ways, such as via case examples, case studies, discussions, and activities. However, the paucity of relevant resources on BoP markets for students to refer to and learn from makes experiential exercises, which entail students venturing out into the field, even more compelling (Satyam & Aithal, 2022; Viswanathan et al, 2016). Next, we explain the importance of experiential learning in general, and its possible use in the context of subsistence marketplaces in particular.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Deo et al (2023), the SDGs can be integrated into marketing education in various ways, such as via case examples, case studies, discussions, and activities. However, the paucity of relevant resources on BoP markets for students to refer to and learn from makes experiential exercises, which entail students venturing out into the field, even more compelling (Satyam & Aithal, 2022; Viswanathan et al, 2016). Next, we explain the importance of experiential learning in general, and its possible use in the context of subsistence marketplaces in particular.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scholars have indicated that many PRME initiatives ignore the complexities of the context where schools are embedded and fail to utilize the learning opportunities provided by the SDGs (Moratis & Melissen, 2022; Parris & McInnis-Bowers, 2017; Voola et al, 2018). Viswanathan et al (2016) argued that the subsistence context has been the most neglected milieu for learning and for informing marketers due to the access challenges therein; they also suggested a bottom-up approach to overcome unfamiliarity. Subsistence marketplaces, otherwise known as base-of-the-pyramid (BoP) markets, have inadequate infrastructure, poor literacy, insufficient markets, high cost of capital, and poor accessibility to services, among other characteristics (Satyam & Aithal, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Gray et al (2012) and Peltier et al (2008) contend experiential activities are critical for preparing students to deal with the challenges of the real-world across different disciplines including business. Examples of commonly used experiential learning activities in business, including marketing and entrepreneurship, include live case studies (Elam & Spotts, 2004), experience simulations (Canhoto & Murphy, 2016), program immersion or immersive projects (Lastner et al, 2016; Viswanathan et al, 2016), retail field trips (Schaller, 2020) and scavenger hunts (Inhofe Rapert & Mukherjee, 2020). The basic dimensions of field-oriented experiential learning include field observations, reflections, and knowledge application (Schaller, 2018).…”
Section: Experiential Learningmentioning
confidence: 99%
“…Viswanathan et al (2016) pointed out that field trips and immersion programs should encourage learning and research at the micro, meso, and macro levels of social analysis.…”
Section: Experiential Learningmentioning
confidence: 99%
See 1 more Smart Citation